The Beneficial Effects of Aerobic Exercise on Human Systems and Organs: A Literature Review - Koman, Anna Maria; Chamera-Cyrek, Katarzyna; Pliszka, Marzena; Janik, Izabela; Gadżała, Katarzyna; Palacz, Karolina Alicja; Kułak, Klaudia Brygida; Sztybór, Izabela (Journal of Education, Health and Sport, 2024)
Introduction: Engaging in regular aerobic exercise can have a tremendous impact on one’s physical and mental well-being. Despite the known benefits, a significant number of adults worldwide continue to lead sedentary lifestyles. Aerobic exercise, in particular, has been shown to improve lipid profiles, reducing the risk of cardiovascular diseases and mortality rates. Additionally, it promotes healthy metabolism, hormonal balance, and mental well-being, all of which contribute to overall health and quality of life. This is especially crucial for cancer patients undergoing treatment. Aim of the Study: The primary objective of this study is to conduct a comprehensive analysis of the physiological and psychological benefits of aerobic exercise on the human body. Description of the State of Knowledge: Moderate and regular aerobic exercise has been shown to have a beneficial effect on both physical and mental health. The importance of improving physical performance, overall body fitness, endurance, strength, balance, and mobility cannot be overstated, as it has a proven therapeutic and preventive effect against various diseases. Materials and methods: An unsystematic scientific literature review was conducted using specific keywords such as earobic exercise, lipid profile, cardiovascular system, cardiovascular disease, diabetes. The review was carried out on PubMed, analyzing a total of 70 sources published until 2023. Conclusions: Exercise has beneficial effects on all organ systems and is a non-pharmacological form of treatment for cardiovascular, musculoskeletal, metabolic and nervous system diseases. They have the benefits of reducing stress, lowering blood pressure, stimulating osteogenesis, and having a beneficial effect on body shape and self-perception. Exercise can be considered an effective treatment for established diseases or the alleviation of their symptoms.